(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The new era of corporate reporting began with the publication of IFRS S1 and S2 as a guide for companies to disclose sustainability reports. Indonesia has not made rules that adopt S1 and S2. The Indonesian government has issued SE OJK 16 2021 as an addition to SE OJK 2016. This research was conducted by mapping between IFRS S1 and S2 and SE OJK 2021; conducting literature studies on the early application of IFRS S1 and S2 in various countries; and made recommendations on indicators for conformity assessment of IFRS S1 and S2 with SE OJK 2021. Based on the results of the research, a fairly high level of conformity was obtained between IFRS S1 and S2 and SE OJK 2021 and not many countries have implemented IFRS S1 and S2. This study also produced recommendations for IFRS S1 and S2 assessment indicators.